Role of Image-Guided Percutaneous Drainage in Pancreatic Collections - Samadi, Katayoun; Arellano, Ronald S. (Digestive Disease Interventions, 2018)
Acute pancreatitis is one of the major gastrointestinal conditions that lead to around 300,000 hospital admissions per year in the United States. While mild inflammation of the pancreas is often managed conservatively, progression of the disease process to necrosis significantly increases the overall morbidity and mortality and often requires surgical or other interventional techniques for management. The purpose of this review is to describe the role of percutaneous drainage for the management of complicated pancreatitis.
Keywords: pancreatitis; Atlanta classification; walled-off necrosis